ON THE IMPLEMENTATION OF SOVIET PERIOD’S LIBRARY WORK DECISIONS IN SAMARKAND REGION - Jiyanbekova Sharofat Abdikaxarovna (American Journals Publishing, 2024)
The history of librarianship and library work is one of the topical issues in every era. Reading books is very necessary in the education of educated and potential young people in society and in the spiritual life of nations. Today, the development of fields in all countries of the world is achieved by creating scientific works, increasing the number of books and publications, adapting libraries to the requirements of the 21st century, and continuing practical research.
Keywords: Library work, librarianship, history of Uzbekistan, former Soviet Union, decisions.